The South China Sea Declaration: A Chinese Perspective - Zhai Kun (2016)
The Declaration on the Conduct of Parties in the South China Sea has not been effective in mitigating tensions among claimant states. To make it more effective, various disputant countries should enhance mutual trust, be open to moral censure for violations and allow external powers to play a more constructive role.